Sugarcane-Legume Intercropping Can Enrich the Soil Microbiome and Plant Growth - Malviya, Mukesh Kumar; Solanki, Manoj Kumar; Li, Chang-Ning; Wang, Zhen; Zeng, Yuan; Verma, Krishan K.; Singh, Rajesh Kumar; Singh, Pratiksha; Huang, Hai-Rong; Yang, Li-Tao; Song, Xiu-Peng; Li, Yang-Rui (Frontiers in Sustainable Food Systems, 2021)
Soil microbes have a direct impact on plant metabolism and health. The current study investigates the comparative rhizobiome between sugarcane monoculture and sugarcane–soybean intercropping. A greenhouse experiment was performed with two treatments: (1) sugarcane monoculture and (2) sugarcane–soybean intercropped. We used a high-throughput sequencing (HTS) platform to analyze the microbial community. We used the 16S rRNA gene and internal transcribed spacer region primers to identify the microbial diversity. HTS results revealed that a total of 2,979 and 124 bacterial and fungal operational taxonomic units (OTUs) were observed, respectively. Microbial diversity results concluded that the intercropping system has a beneficial impact on soil microbes. The highest numbers of bacterial and fungal OTUs were found in the intercropping system, and these results also collaborated with quantitative PCR results. Additionally, intercropped sugarcane plants showed a higher weight of above- and below-ground parts than the monoculture. Soil chemical analysis results also complemented that the intercropping system nourished organic carbon, total nitrogen, and soil enzyme activities. Correlation analysis of the diversity index and abundance concluded that soil nutrient content positively influenced the microbial abundance that improves plant growth. The present study frames out the profound insights of microbial community interaction under the sugarcane–soybean intercropping system. This information could help improve or increase the sugarcane crop production without causing any negative impact on sugarcane plant growth and development.